Effect of methanolic extracts of periwinkle (Vinca rosea) and bottlebrush (Callistemon lanceolatus) alone and their mixtures against neonate larvae of gram pod borer (Helicoverpa armigera) - HALDER, JAYDEEP; SRIVASTAVA, CHITRA; DUREJA, PREM (The Indian Journal of Agricultural Sciences, 2011)
The insect growth regulatory, cumulative larval mortality and adult inhibitory activity of methanolic extracts of ‘Sadabahar’ (Vinca rosea L.) and bottle brush (Callistemon lanceolatuts L.) alone and their mixtures at different ratios were evaluated against the neonate larvae of Helicoverpa armigera (Hubner) by artificial diet incorporation method. It has been recorded that highest growth regulatory activity (GI50) was noticed at 1 : 3 mixture both in 7 and 9 days of treatment (62, 69 ppm), followed by 1 : 1 (70, 77 ppm) and 3:1 (81, 83 ppm). Same trend was also observed for cumulative larval mortality (LC50) and adult inhibitory activity (I50) and the values were 80, 101, 127 and 36, 40, 47 ppm, respectively. Incorporation of both extracts and their mixtures at different ratios into the artificial diet significantly reduced the larval growth as compared to control. Among the two plants tested, V. rosea was showed higher growth regulatory activity and larval toxicity than C.lanceolatus. However, the adult inhibitory activity was more in C.lanceolatus (72 ppm) than V. rosea (76 ppm).